The EU Services Directive : Gains from Further Liberalization - Corugedo, Emilio Fernandez (IMF Working Papers; Working Paper, 2014)
The EU Services Directive was adopted in 2006 to foster competition in services across Europe. However, progress in liberalizing services has fallen short of expectations due to the article 15 of the Directive, which allows countries to maintain pre-existing restrictions if judged necessary to protect the public interest. Through input output analysis, this paper finds important multiplier effects of greater efficiency services to the rest of the economy. A renewed impulse to the liberalization process could be given by enhancing the advocacy role of national competition authorities in interpreting the notion of public interest underpinning existing regulations.